Characterization of Spodoptera litura Gut Bacteria and Their Role in Feeding and Growth of the Host - Xia, Xiaofeng; Lan, Bomiao; Tao, Xinping; Lin, Junhan; You, Minsheng (Frontiers in Microbiology, 2020)
Insect gut microbes play important roles in host feeding, digestion, immunity, growth and development. Spodoptera litura is an important agricultural pest distributed of global importance. In the present study, diversity and functions of the gut bacteria in S. litura are investigated based on the approaches of metagenomics and denaturing gradient gel electrophoresis (DGGE). The results showed that the gut bacterial diversity of S. litura reared on taro leaves or an artificial diet, were similar at the phylum level, as both were mainly composed of Proteobacteria, but differed significantly at the order level. Spodoptera litura reared on taro leaves (Sl-tar) had gut biota mainly comprised of Enterobacteriales and Lactobacillales, while those reared on artificial diet (Sl-art) predominantly contained Pseudomonadales and Enterobacteriales, suggesting that gut bacteria composition was closely related to the insect’s diet. We found that feeding and growth of S. litura were significantly reduced when individuals were treated with antibiotics, but could be both restored to a certain extent after reimporting gut bacteria, indicating that gut bacteria are important for feeding, digestion and utilization of food in S. litura. Metagenomic sequencing of gut microbes revealed that the gut bacteria encode a large number of enzymes involved in digestion, detoxification and nutrient supply, implying that the gut microbes may be essential for improving the efficiency of food utilization in S. litura.